Human Capital Management as a Driver of Organizational Performance: A Literature Review: JEL Classification: J24, J28, J81, M12, I31, M54 - Karmilah Karmilah; Orfyanny Syahreffy Themba; Ismail Ismail (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to systematically examine how Human Capital Management (HCM) contributes to organizational performance by synthesizing existing empirical and review-based literature. The review seeks to identify core mechanisms, enabling conditions, and performance pathways through which HCM operates as a strategic organizational system. A systematic literature review (SLR) approach was employed to analyze fifteen peer-reviewed studies published between 2013 and 2025. Relevant articles were identified through a structured search of academic databases using keywords related to human capital management, organizational performance, innovation, leadership, and human capital development. The selected studies were screened using predefined inclusion and exclusion criteria and analyzed through thematic synthesis with an interpretative orientation. The synthesis reveals four dominant themes that consistently explain the performance effects of HCM: competency development as the core mechanism, organizational innovation as an outcome and mediating process, transformational leadership as an enabling condition, and performance infrastructure as a motivational system. The findings indicate that HCM enhances organizational performance when human capital development is integrated with organizational strategy, supported by leadership, and reinforced by aligned reward and appraisal systems. The review concludes that HCM functions most effectively as an integrated strategic architecture rather than a set of administrative HR practices. Its impact on performance is contingent upon contextual alignment, leadership support, and institutionalized development systems. These findings provide a comprehensive framework for advancing both research and practice on strategic human capital management.